Legal regulation of the restoration and use of international financial assistance under martial law in Ukraine - Манько, Денис Григорович; Манько, Д. Г.; Manko, Denys H.; Іванченко, Ольга Миколаївна; Іванченко, О. М.; Ivanchenko, Olha M.; Іванчук, Віра Євстафіївна; Іванчук, В. Є.; Ivanchuk, Vira Ye. (Riga : Baltija Publishing, 2025)
This study examines the legal and institutional framework governing the attraction, distribution and control of international financial assistance in Ukraine under martial law. The paper focuses on how constitutional principles, fiscal governance, anti-corruption mechanisms and digital transparency interact to ensure the lawful and efficient use of external aid during the war. Methodology. The research is grounded in a synthesis of comparative-legal, systemic, and institutional-economic methodologies. The programme integrates constitutional analysis, evaluation of executive and financial legislation, and assessment of international agreements with the IMF, EU, and World Bank. This methodological approach facilitated the identification of the interdependence between economic stability, legal accountability, and institutional resilience. The aim of the work is threefold: firstly, to define the legal architecture of Ukraine's wartime financial governance; secondly, to assess its conformity with international standards; and thirdly, to develop proposals for strengthening the legal mechanisms of transparency, parliamentary control, and post-war reconstruction management. The results of the study demonstrate that the Ukrainian system of international financial assistance functions as a hybrid legal institution, integrating constitutional order, emergency flexibility, and multilateral conditionality. The IMF Extended Fund Facility, the EU Ukraine Facility, and the World Bank PEACE programme have been shown to stabilise the economy and promote institutional modernisation through legal reforms and anti-corruption benchmarks. The results of the study demonstrate that the Ukrainian system of international financial assistance functions as a hybrid legal institution, integrating constitutional order, emergency flexibility, and multilateral conditionality. The IMF Extended Fund Facility, the EU Ukraine Facility, and the World Bank PEACE programme have been shown to stabilise the economy and promote institutional modernisation through legal reforms and anti-corruption benchmarks. Conclusion. The legal regulation of international financial aid in wartime constitutes both an economic and constitutional function of the state. Ukraine's experience demonstrates that adherence to the rule of law, digital transparency, and institutional accountability can transform donor support from a survival mechanism into an instrument of modernisation and post-war development. The country's future economic security is contingent on the institutionalisation of wartime innovations within a stable legal framework that is aligned with European governance standards.
Manko D. Legal regulation of the restoration and use of international financial assistance under martial law in Ukraine / D. Manko, O. Ivanchenko, V. Ivanchuk // Baltic Journal of Economic Studies. – Riga : Baltija Publishing, 2025. – 11(5). - P. 223-231. URL: https://doi.org/10.30525/2256-0742/2025-11-5-223-231
Keywords: international financial assistance; legal regulation; administrative procedure; economic security; institutional resilience; wartime governance; anti-corruption; digital transparency; good governance; Ukraine